East African runners: Their genetics, lifestyle and athletic prowess - Onywera, V. O. (Genetics and Sports, 2009)
East African runners have dominated distance running events for over 5 decades. Some explanations have been advanced to explain why such a small population has dominated distance running events over time. Suggested reasons include, among others, a genetic predisposition, diet, living at high altitude as well as sociocultural background. This chapter gives possible insight into the past, present and hopefully future success of East African runners; it mainly explores the foundations of running excellence, talent identification, diet and injury management methods used by East African runners. The chapter also explores means and ways by which East African runners can sustain their running excellence by using their past experiences, to perfect the present and predict the future. (Autorreferat)